Phenolic profile, antioxidant and antiproliferative activities of Convolvulus aucheri Choisy - Ozay Cennet; Mammadov Ramazan (Vojnosanitetski Pregled)
Background/Aim. It is known that some members of the genus Convolvulus (C) L. are commonly used in Turkish folk medicine. These species are powerful in curing toothache and joint pains. Due to the limited information on the biological activities of C. aucheri, a species almost exclusively occurring in Turkey, we aimed to investigate the antioxidant and cytotoxic effects of three extracts obtained from the plant, as well as to characterize their phenolic profile. Methods. The anti-oxidant activity of the extracts was determined by using ABTS, NO, FRAP, phosphomolybdenum, and metal chelating assays. In addition, the bioactive compounds found in the extracts, such as total phenolics, flavonoids, and saponins, were determined. Cytotoxicity was assessed by using the CellTiter-Glo assay on HeLa and H1299 cancer cells. Results. The methanol extract of C. aucheri demonstrated the highest antioxidant activity as well as the highest phenolic, flavonoid, and saponin content. The high-performance liquid chromatography (HPLC) analysis showed that the major phenolic compounds in the extract were chlorogenic acid, (+)-catechin, rosmarinic acid, and rutin. The methanolic extract obtained from the aerial parts of C. aucheri was found to interfere with the viability of HeLa cells, with an IC50 value of 14.22 μg/mL being recorded. Conclusion. Our results showed that C. aucheri could be a good candidate as a novel and alternative natural antioxidant and antitumor source.